2002
DOI: 10.1002/bdd.299
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and receptor‐site binding of 125I‐EGF after topical administration to skin wounds

Abstract: The rhEGF topical delivery systems have been hindered by a number of shortcomings which have led to the search of new development strategies. In this study we report the evaluation of cumulative profiles of 10, 5 and 1 microg/ml solutions of (125)I-rhEGF, in a rat full-thickness skin wound model, as well as the drug-induced modulation in the expression of the EGF receptor after lesion. The tissue-associated radioactivity, expressed as the percentage of the dose administered per grams of tissue (%D/g), peaks at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…The idea of a direct action on rat luteal cells is reinforced by the demonstration of high-affinity, low-capacity EGF-binding sites in these cells (38). On the other hand, EGF peptide is rapidly degraded after in vivo administration (39,40). We demonstrated that EGF is exerting its effect through the second mechanism.…”
Section: Discussionmentioning
confidence: 79%
“…The idea of a direct action on rat luteal cells is reinforced by the demonstration of high-affinity, low-capacity EGF-binding sites in these cells (38). On the other hand, EGF peptide is rapidly degraded after in vivo administration (39,40). We demonstrated that EGF is exerting its effect through the second mechanism.…”
Section: Discussionmentioning
confidence: 79%
“…It was somewhat surprising as other studies had already established proteolysis on GFs and their receptors in chronicity circumstances [133]. Further evaluations of cumulative profiles of radiolabeled EGF in a rat full-thickness wound model showed EGF degraded subspecies and a short residence time within the wound contours [134]. We had the experience of injecting EGF locally into denervated rat hind limbs upon sciatic nerve full-thickness cut.…”
Section: The Rationale For a Novel Delivery Procedure Egf Intralesiomentioning
confidence: 95%
“…125 I-labelled tumour growth factor beta (TGF-β) has been used for the study of angiogenesis [30] and radiolabelled epidermal growth factor (EGF) has been used for the study of metastatic lymph nodes, for imaging breast cancer and for the study of skin wounds [31,32,33]. Most radiolabelled cytokines have been used for the study of inflammatory diseases, e.g.…”
Section: Radiolabelled Cytokinesmentioning
confidence: 99%